FENDRR Affects COAD Biological Behavior by Inhibiting the DUSP4/CREB/PRKACB Pathway - Hao Zhang; Li Hong; Zirui Zhuang; Qiange Zhang; Feng Zhang; Ruipeng Wang; Jinjing Xu; Youyuan Tang; Xingpo Guo; Ling Gao (International Journal of Genomics)
Conclusion: We establish FENDRR as a tumor-suppressing gene that plays a significant role in suppressing the advancement and metastatic spread of COAD. These findings underscore its diagnostic and prognostic utility in COAD.